Identification of heel bone mineral density as a risk factor of Alzheimer’s disease by analyzing large-scale genome-wide association studies datasets - Gao, Feng; Pan, Rongrong; Fan, Taixuan; Liu, Lingling; Pan, Haile (Frontiers in Cell and Developmental Biology, 2023)
Both low bone mineral density (BMD) and Alzheimer’s disease (AD) commonly co-occur in the elderly. Until now, the association between AD and BMD has been widely reported by observational studies. However, Mendelian randomization (MR) studies did not support the causal association between BMD and AD. We think that the lack of significant causal association between AD and BMD identified by recent MR studies may be caused by small number of potential instrumental variables. We conduct a MR study to evaluate the causal effect of heel BMD on the risk of AD using 1362 genome-wide significant and independent (P < 5.00E-08) heel BMD genetic variants as the potential instrumental variables, which are identified by a large-scale genome wide association study (GWAS) of heel BMD in 394,929 UK Biobank individuals. Using these 1362 genome-wide significant and independent heel BMD genetic variants, we extracted their corresponding AD GWAS summary results in IGAP AD GWAS dataset (n = 63926) and FinnGen AD GWAS dataset (n = 377277). Five methods including inverse-variance weighted meta-analysis (IVW), weighted median, MR-Egger, MR-PRESSO, and MRlap were selected to perform the MR analysis. 951 of these 1362 genetic variants are available in AD GWAS dataset. We observed statistically significant causal effect of heel BMD on the risk of AD using IVW in IGAP AD GWAS dataset (OR = 1.048, 95% CI: 1.002 – 1.095, P = 0.04) and FinnGen AD GWAS dataset (OR = 1.053, 95% CI: 1.011 – 1.098, P = 0.011). Importantly, meta-analysis of IVW estimates from IGAP and FinnGen further supported the causal effect of heel BMD on the risk of AD (OR = 1.051, 95% CI: 1.02 – 1.083, P = 0.0013). Collectively, our current MR study supports heel BMD to be a risk factor of AD by analyzing the large-scale heel BMD and AD GWAS datasets. The potential mechanisms underlying the association between heel BMD and AD should be further evaluated in future.